Snijders Blok–Campeau Syndrome Associated with Pulmonary Arterial Hypertension: A Case Report - Luisa Paul; Victoria C. Ziesenitz; Matthias Gorenflo (Reports)
Background and Clinical Significance: We report on an infant with Snijders Blok–Campeau syndrome (psychomotor developmental delay, CNS malformations) and a complex heart defect with pulmonary arterial hypertension. Case Presentation: A DDX3X mutation encoding for RNA helicase was detected, which may suggest an association between Snijders Blok–Campeau syndrome and the development of pulmonary vasculopathy. However, further validation is required. Conclusions: We suggest an important role for DDX3X in the development of the pulmonary vasculature.